Global politics and the responsibility to protect : from words to deeds - Bellamy, Alex J., 1975- (Global politics and the responsibility to protect., 2011)
This book provides an in-depth introduction to, and analysis of, the issues relating to the implementation of the recent Responsibility to Protect principle in international relations.